La comunicación asertiva y las relaciones interpersonales de los servidores públicos de la Municipalidad Distrital de Vargas Guerra periodo 2024 - Vela Macedo, Paula Sofia (2025)
The objective was to examine the influence of assertive communication on the interpersonal relationships of public servants of the Municipality District of Vargas Guerra 2024. This investigation is fundamental, explanatory, quantitative, with a non-experimental, transversal and causal correlational design. The studied population consists of 181 public servants, and the sample is as large as the population, thus using the population census. The survey technique was used with a 26-item questionnaire on assertive communication and 33 on interpersonal relationships, using an ordinal scale for measurement. 68% of employees believe that there is good assertive communication, and 32% say that there is regular communication. 68% consider interpersonal relationships to be satisfactory and 32% perceive something satisfactory. The first dimension of the communication style and the second dimension of his direction show a weak positive correlation, with both having a direct influence on interpersonal relationships. No significant association was found between the demographic profile of public servants and their interpersonal relationships. It is determined that there is a moderate positive causal relationship (Rho 0.495, p value =0.000) between assertive communication and interpersonal relationships perceived by public servants of the Municipality District of Vargas Guerra, period 2024, which indicates that assertive communication improves interpersonal relationships.